Odpowiedzi

2010-03-15T17:50:17+01:00
A² -3a+1 dla a = -4
(-4)² - 3 * (-4)+1 = 16+12+1 = 29

1+x(x+4) dla x = -11
1+x²+4x = 1+ (-11)² +4 * (-11) = 1+121 - 44 = 78

x-2y dla x = 1 i dla y = -1
1-2 * (-1) = 1+2 = 3

2x² -y(x+1) dla x = -2 i y=5
2x² -yx-y = 2* (-2)² - (5* -2)-5 = 2*4 +10-5 = 8+10-5 = 13

(m+1)(n-2) dla m =2 dla n=1
mn-2m+n-2 = 2*1 - 2*2+1-2 = 2-4+1-2 = -3
2010-03-15T17:55:01+01:00
A²-3a+1=-4²-3×(-4)+1=16+12+1=29

1+x(x+4)=1-11×(-11+4)=1-11×(-7)=1+77=78

x-2y=1-2(-1)=1+2=3

2x²-y(x+1)=2×(-2)²-5×(-2+1)=2×(-4)-5×(-1)=8-(-5)=8+5=13

(m+1)(n-2)=(2+1)(1-2)=3×(-1)=-3
Najlepsza Odpowiedź!
2010-03-15T18:00:12+01:00
A= - 4
a² -3a+1=(-4)²-3*(-4)+1=16+12+1=29

x=-11
1+x(x+4)=1+x²+4x=1+(-11)²+4*(-11)=1+121-44=78

x=1 y= -1
x-2y=1-2*(-1)=1+2=3

x = -2 y=5
2x²-y(x+1)=2x²-yx-y=2*(-2)²-5*(-2)-5=8+10-5=13

m =2 n=1
(m+1)(n-2) =(2+1)(1-2)=3*(-1)=-3